Critical discourse analysis in new media: theoretical and methodological challenges - Dehghan, Ehsan; Mohamad Ali, Afida (Malaysian Association of Modern Languages, 2015)
This paper investigates the range of theoretical and methodological challenges facing scholars attempting to do studies employing Critical Discourse Analysis (CDA) in the context of New Media, such as participatory web platforms, social networking websites, or online forums. The rise and popularity of Web 2.0 has attracted researchers from diverse fields of academic inquiry to this area. However, CDA scholars had not paid attention to these domains until recently. The specific features of Web 2.0 spaces create a multitude of challenges for a (critical) discourse analyst, ranging from issues of language, to problems of data collection and applicable theoretical frameworks. Drawing from the existing literature, and also experiences gained through a CDA study on Facebook discourses, this article will discuss these challenges, the current state of affairs, and the limitations of doing discourse analytical studies in New Media.